Bi’ah Islamiyah as a spiritual resilience framework: Implementation, internalization strategies and its impact on students in the digital disruption era - Frendy Sasongko; Bagus Jamroji; M. Alfi Syahrin (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
In the digital disruption era, fostering students’ spiritual resilience has emerged as a critical challenge for Islamic Religious Education (IRE). Nevertheless, empirical research examining the integration of bi’ah Islamiyah as a holistic framework for cultivating students’ spiritual resilience within IRE remains limited. This study aims to explore the implementation of bi’ah Islamiyah , the strategies employed to internalize spiritual values, and their impact on students’ spiritual resilience in the context of digital disruption. The methodology used is a descriptive qualitative approach. Data was obtained through in-depth interview techniques and analyzed using a thematic categorization method adapted to the Miles and Huberman interactive model. Furthermore, triangulation is used to ensure the credibility of the data generated. The results indicate that bi’ah Islamiyah plays a strategic role in strengthening students’ spiritual resilience through the integration of formal learning activities and extracurricular programs. Teachers internalize spiritual values by embedding them within the curriculum, cultivating a religious school culture, and demonstrating exemplary conduct. The implementation of bi’ah Islamiyah positively contributes to students’ discipline, digital self-regulation, inner well-being, and the development of a religious school environment. This study contributes to the advancement of IRE by providing an empirical foundation for developing spiritually resilient learners in the digital era and offers a practical framework for fostering a sustainable religious school culture. The originality of this study lies in integrating the concept of bi’ah Islamiyah with spiritual resilience as a comprehensive pedagogical framework for IRE in the context of digital disruption.